(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
The human heart is a muscular organ that functions as the central pump of the circulatory system, delivering oxygenated blood to tissues and organs while removing metabolic waste. It consists of four chambers—two atria and two ventricles—separated by valves that ensure unidirectional blood flow. This thesis examines the detailed anatomy of the heart, its physiological mechanisms including the cardiac cycle and electrical conduction system, and common pathophysiological conditions such as coronary artery disease, heart failure, and arrhythmias. Understanding the heart’s normal function and common disorders is essential for the development of effective diagnostic and therapeutic strategies.